Student and Faculty Beliefs about Diverse Approaches to Engineering Design Decisions - Emily Dringenberg (VT Publishing, 2021)
Background: Engineers need to be able to make robust design decisions. Because design is an ill-structured endeavor, design decisions require some combination of rationalistic, intuitive, and empathic approaches. However, engineering education remains largely oriented towards the use of rationalistic approaches. Purpose/Hypothesis: We posit that the persistent gap between the need to leverage diverse approaches to make engineering design decisions and the emphasis on primarily rationalistic approaches in engineering spaces is due, in part, to the beliefs that individuals hold about diverse approaches. Design/Method: We analyzed interview transcripts to identify the beliefs shared by students and by faculty (as individual units of analysis) about rationalistic, intuitive, and empathic approaches to making engineering design decisions, and then we compared the shared beliefs of the two groups. Results: Students and faculty similarly shared a belief that rationalistic approaches are normative in engineering. The two groups also had a common, general belief that empathic approaches are missing in engineering, but they differed in the ways in which they talked about empathic approaches. Finally, the two groups differed in their beliefs about the role of diverse approaches in practice: students believed rationalistic approaches are and should be used most in practice, but faculty believed that rationalistic approaches are inherently limited and therefore require the use of intuitive approaches. Conclusions: We interpret the pervasive belief that engineers are expected to portray their design decision making as primarily rational as a reflection of an unrealistic yet powerful social norm in engineering spaces, which can be understood as a key part of how the exclusive culture of engineering is perpetuated. We see a need to teach explicitly about this social norm in order to disrupt it, and we encourage engineering educators to reflect on how the ways in which their praxis might endorse or reinforce such unrealistic beliefs, either explicitly or implicitly.